Teknik Ceklis sebagai Asesmen Perkembangan Sosial Emosional di RA Insan Mulia Bambanglipuro - Hasanah, Fitria Fauziah; Latif, Muhammad Abdul (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2019)
This study aims to analyze the use of checklist techniques as an assessment to determine the emotional social development of early childhood. The method used in this research is descriptive qualitative by describing checklist techniques as an assessment used to determine emotional social development. This research uses data collection techniques including observation, interviews and documentation conducted at RA Insan Mulia Bambanglipuro, Bantul, Yogyakarta. Based on the results of research that has been carried out shows that RA Insan Mulia Bambanglipuro implement assessment techniques to assess the development of their students using three techniques namely checklist techniques, anecdotal notes and the work. including for assessing social emotional development using all three techniques, but one of the most prominent techniques to use is the checklist technique. This checklist technique is used by RA Insan Mulia in accordance with the 2015 Early Childhood Education Learning Assessment Guidelines, Ministry of Education and Culture Directorate General of Early Childhood Education and Community Education in 2015.